Analisis Pemahaman Guru Dalam Menggunakan Limbah Jagung Sebagai Media Pembelajaran di RA Al Amien - Mayangsari, Dewi; Suci Rahmawati, Dewi; Nurhayati Adhani, Dwi (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study was conducted to understand teachers' comprehension in utilizing corn waste as a learning medium at RA Al Amien. This research employs a qualitative model with a sample size of 12 educators at RA Al Amien. Data collection techniques include semi-structured interviews, tests, and documentation. The data analysis process is carried out using the Miles & Huberman analysis model, including 1) Data reduction, 2) Data display, 3) Conclusion drawing. The research findings indicate that the level of teachers' understanding at RA Al Amien in using corn waste as a learning medium is good, but not yet optimal. This is due to a lack of training, development, and understanding among teachers about the utilization of corn waste in early childhood education. Obstacles faced by teachers at RA Al Amien regarding the use of corn waste as a learning medium include limited teacher knowledge, making it not yet considered for use in the learning process. A follow-up suggestion from this study is to strive for training on the utilization of corn waste for educators so that they can create interesting and enjoyable learning media for children.